Social Adjustment Mahasiswa Asing di Wilayah Surabaya Raya - Khotijah, Siti; Hidayah, Nurul (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
The aim of this research is to find out and describe the experiences and challenges related to the social adjustment of foreign students in the Greater Surabaya area. This research uses a type of qualitative research using a phenomenological approach. The informants in the research were 5 foreign students from outside the Southeast Asia region. These foreign students come from 5 countries, namely Palestine, Sierra Leone, South Korea, China and Yemen and are currently studying at various universities in the Greater Surabaya area. The technique for selecting informants is using purposive sampling. The data collection method was carried out using in-depth interviews and documentation. The data analysis technique in this research is content analysis. This analysis technique is a method designed to identify and interpret meaning in the form of communication recordings, texts, images and isolate small parts of the data that represent to describe or explain a phenomenon. The results of the research show that foreign students in Greater Surabaya understand cultural awareness, willingness to acceptance of new cultural values, a proactive attitude to learning, and prior study preparation. Factors influencing the social adjustment of foreign students in the Greater Surabaya Region are social support, individual personality, and readiness to learn which also play a role in the process of social adaptation in a new environment.